The Reception of Graham Harman’s Philosophy in Polish and Ukrainian Scholarship - Vasyl Korchevnyi (Kyiv-Mohyla Humanities Journal)
The article aims to explore the ways in which scholars from Poland and Ukraine engage with Graham Harman’s philosophical work1 . The introductory part briefly describes Harman’s ontology and demonstrates the link connecting Harman with Polish and Ukrainian intellectual environments. Harman’s object-oriented ontology (OOO) states that objects are the fundamental building blocks of reality and cannot be reduced either to what they are made of or to what they do, that is, either to their constituents or to their effects. The connection with Poland and Ukraine goes back to the theory of objects suggested by the Polish philosopher Kazimierz Twardowski, whom Harman names among the predecessors of his ontology and who influenced both Polish and Ukrainian intellectual milieus. The next part of the article examines the history of the reception, identifying its key events and publications. The reception in Poland proves to be much more substantial than in Ukraine. A common tendency is determined: a conflation of Harman’s OOO and speculative realism by mistakenly ascribing the features of the former to the latter (broader concept), which suggests that speculative realism is being received through the lens of Harman’s project. The next part establishes the key discursive points that are used to map Harman’s ideas within the contemporary philosophical landscape. They can be summarised by the terms antianthropocentrism and antireductionism. The final part analyses the strategies for applying Harman’s theory showing that it can become the lens for interpretation and direct our attention to nonhumans and the hidden, inexplicable dimension of things or provide an ontological grounding for semi-literary and literary discourses. The methodology of this application, though, needs further development and clarification. Overall, in Poland, two of Harman’s books and two articles have been translated, and at least two books, one Ph.D. dissertation, and around two dozen articles discuss or apply his ideas. Apart from philosophy, his OOO is used for discussing literature, video games, films, humanities in general, education, management processes, antique studies, and ecocriticism. In Ukraine, one of Harman’s articles has been translated, and around ten articles and one collective monography engage with his philosophical project. Some of the Ukrainian works also apply Harman’s OOO in contexts that are not strictly philosophical, namely, in literary criticism, urban studies, film studies, and humanities in general. This paper can be of use to researchers studying OOO and its reception in different countries. In addition, it can help Ukrainian and Polish scholars who want to discuss or use OOO to familiarize themselves with the previous reception in their countries, thus facilitating domestic philosophical interaction.